PENGARUH GAYA KEPEMIMPINAN TRANSFORMASIONAL, KOMITMEN AFEKTIF, KOMITMEN KONTINUANS DAN KOMITMEN NORMATIF TERHADAP KESIAPAN BERUBAH (Studi pada Bank BRI Kantor Wilayah Yogyakarta) - Putri Oktovita Sari (Fakultas Ekonomi, Universitas Sanata Dharma Yogyakarta, 2018)
The Purpose of this research is to Examine the influence between transformational leadership, commitment on readiness to change. Transformational leadership and organizational commitment are the key factors to support readiness to change. Transformational leadership contributes to change employee commitment and push employee participation within readiness to change. Commitment divined by affective commitment, continuity commitment, and normative commitment on readiness to change. This research evaluates the reaction of leader and employee commitment to the change of business strategy in BRI Kanwil Yogyakarta. Methode of this research is Multiple regression. With distributedquestionnaireto 100 employees. The result of this research is thereeffect between transformational leadership on readiness to change, there is effect between affective commitment organizational on readiness to change, there is effect continuity commitment on readiness to change, and there is effect normative commitment on readiness to change.